-35=1+49n

Simple and best practice solution for -35=1+49n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -35=1+49n equation:



-35=1+49n
We move all terms to the left:
-35-(1+49n)=0
We add all the numbers together, and all the variables
-(49n+1)-35=0
We get rid of parentheses
-49n-1-35=0
We add all the numbers together, and all the variables
-49n-36=0
We move all terms containing n to the left, all other terms to the right
-49n=36
n=36/-49
n=-36/49

See similar equations:

| -1+16p=12+15p | | 2(7-5x)=24 | | -t/8=7 | | 1/2+16=2/3x-4 | | 4x+9=3x–2 | | 1/3(6x-5)-x=1/3-2(x-1 | | -14j+15=5-3-13j | | 8+x-2=2+3x | | -3=4y+1 | | .2+2m=2.2 | | -10+19c+15=20+18c | | -16=30x | | 3x-19=42 | | 4+-c=-12 | | 3x+22=5x-7 | | -5(2-z)=10 | | -(a-2)=-14 | | 6x+24-8x=10 | | 3(2w-12)=24w | | 5(x+6)+10=60 | | (3x+5)(3x+5)=(x+1)(x+1) | | 4+-c=12 | | 5+x=-24 | | 34=8x-30 | | 2p-2-5p=10 | | 16.02=3g+3.63 | | 11y-4-2y=59 | | 11x+77=30x-40-6x | | -6y+12=2(y-2) | | 5x–3=2–(3x–3) | | 8x-20/12=2x-7 | | 2x-4(x-2)=-4+3x-3 |

Equations solver categories